Analysis of the Effectiveness of Health Programs on Access to Public Health Services (Case Study at BPJS Kesehatan Marelan) - Syahputri, Dea Aulia; Atika; Rahma, Tri Inda Fadhila (Ilomata International Journal of Social Science, 2025)
The topic is highly relevant to public health and social policy, particularly in developing country contexts undergoing universal health coverage transitions.This study evaluates the effectiveness of the National Health Insurance (JKN) program managed by BPJS Kesehatan in the Marelan area of Medan. This study examines how the BPJS Kesehatan program improves access to health services for low-income groups. Using a qualitative case study design, the research involved in-depth interviews and observations at several local healthcare facilities. Participants included BPJS users in Marelan with diverse demographic backgrounds. Data were analyzed thematically. The obstacles include long waiting times, limited facilities and medicines, and low public understanding of their rights and obligations. Additionally, socioeconomic factors affect access, with low-income groups facing additional barriers. The study implies the need to improve health infrastructure, simplify administrative procedures, adopt an inclusive approach targeting vulnerable populations, and enhance program socialization to raise public awareness. Implementing these recommendations is expected to improve the quality of BPJS Kesehatan services and health outcomes in the Marelan community.